2012
DOI: 10.1161/hypertensionaha.111.190017
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Dairy Food Intake and Arterial Stiffness

Abstract: Modifiable risk factors, such as diet, are becomingly increasingly important in the management of cardiovascular disease, one of the greatest major causes of death and disease burden. Few studies have examined the role of diet as a possible means of reducing arterial stiffness, as measured by pulse wave velocity, an independent predictor of cardiovascular events and all-cause mortality. The aim of this study was to investigate whether dairy food intake is associated with measures of arterial stiffness includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 46 publications
5
79
1
Order By: Relevance
“…The few intervention studies (94,123,128,136,(145)(146)(147)(148) that have assessed the effects of milk and dairy product consumption on glucose and insulin concentrations to date were included in a recent systematic review and meta-analysis by Benatar et al (149) . This showed that there was no significant change in fasting blood glucose between high-and low-fat dairy diets (overall mean change 1·32, 95 % CI 0·19, 2·45 mg/dl; 0·073, 95 % CI 0·011, 0·136 mmol/l).…”
Section: Blood Glucose and Insulin Resistancementioning
confidence: 99%
“…The few intervention studies (94,123,128,136,(145)(146)(147)(148) that have assessed the effects of milk and dairy product consumption on glucose and insulin concentrations to date were included in a recent systematic review and meta-analysis by Benatar et al (149) . This showed that there was no significant change in fasting blood glucose between high-and low-fat dairy diets (overall mean change 1·32, 95 % CI 0·19, 2·45 mg/dl; 0·073, 95 % CI 0·011, 0·136 mmol/l).…”
Section: Blood Glucose and Insulin Resistancementioning
confidence: 99%
“…, and like blood pressure (2) , may be influenced by dairy food intake (3) . Few studies have investigated the effects of consumption of these foods on prospective measures of arterial stiffness.…”
mentioning
confidence: 99%
“…Our most recent search of the literature (November 27, 2012) indicated no cross-sectional or prospective examination of dairy consumption in relation to this important outcome variable, other than our recent study. 3 In a sample of 587 community-based participants of the MaineSyracuse Study (58% men, mean age 65, SD=12), stroke and dementia excluded, we reported a statistically significant linear cross-sectional relation between self-reported dairy intake, PWV, systolic blood pressure, and pulse pressure, but found no significant association between dairy intake and diastolic blood pressure, total cholesterol, low-density lipoprotein-cholesterol, or high-density lipoprotein-cholesterol. This was true for a basic model adjusting for age, sex, education, and race, as well as an extended model additionally adjusted for height and weight (or waist circumference), heart rate, antihypertensive drug treatment, mean arterial pressure, the lipid values, depressed mood, grains per day, vegetables per day, sweets per day, protein per day, and total food servings per day.…”
Section: To the Editormentioning
confidence: 70%